Upaya meningkatkan hasil belajar PPKn tema 4 sehat itu penting dengan strategi synergetic teaching peserta didik kelas V sekolah dasar - Mulyani, Sri (Jurnal Pendidikan Dasar, 2023)
The purposes of this research are describing and analyzing the improvement of the Citizen Education learning output on the 4th Theme about the Importance of the Healthy with the Synergetic Teaching Method of the V Grade Students of Jukung Elementary School on the First Semester of the 2022/2023 Academic Year. This research is a Classroom Action Research (CAR). The place is on the V Grade of Jukung Elementary School. The moment is on end period of the First Semester of the 2022/2023 Academic Year. The subjects are 23 students; consist of 17 boys and 6 girls. Techniques of collecting data are nontest and test. Tools of collecting data are sheet of observations, activities documentation and written test. Technique of analyzing data is descriptive comparative, according to data type. The action succeed indicator is learning output included to the good. The procedure of this research is cycle model. The result of this research is the Citizen Education learning output improved from bad into good. On the Early Condition, the average is 66,521 and the completeness is 34,782%. Meanwhile on the II Cycle, the average is 80 and the completeness is 82,608%.